2014
DOI: 10.1111/2049-632x.12204
|View full text |Cite
|
Sign up to set email alerts
|

Protein- and DNA-based anthrax toxin vaccines confer protection in guinea pigs against inhalational challenge withBacillus cereusG9241

Abstract: In the past decade, several Bacillus cereus strains have been isolated from otherwise healthy individuals who succumbed to bacterial pneumonia presenting symptoms resembling inhalational anthrax. One strain was indistinguishable from B. cereus G9241, previously cultured from an individual who survived a similar pneumonia-like illness and which was shown to possess a complete set of plasmid-borne anthrax toxin-encoding homologs. The finding that B. cereus G9241 pathogenesis in mice is dependent on pagA1-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Fortunately, as the mechanism of pathogenicity is the same through production of tripartite anthrax toxin, it is highly likely that current anthrax vaccines will provide effective immunity against the atypical B. cereus and Bcbva strains (Oh et al, 2013;Palmer et al, 2014;Brézillon et al, 2015). The bacteria are also susceptible to frontline antibiotics, though administration of secondary β-lactamase antibiotics (such as penicillin) may have reduced efficacy due to inherent resistance in many B. cereus strains (Table 4; Klee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, as the mechanism of pathogenicity is the same through production of tripartite anthrax toxin, it is highly likely that current anthrax vaccines will provide effective immunity against the atypical B. cereus and Bcbva strains (Oh et al, 2013;Palmer et al, 2014;Brézillon et al, 2015). The bacteria are also susceptible to frontline antibiotics, though administration of secondary β-lactamase antibiotics (such as penicillin) may have reduced efficacy due to inherent resistance in many B. cereus strains (Table 4; Klee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As the toxins expressed by atypical B. anthracis and Bcbva strains are homologous to those produced by B. anthracis, it is hypothesized that these currently licensed vaccines will provide adequate protection against anthrax-like disease caused by B. cereus. Studies in C57BL/6 mice and Dunkin Hartley guinea pigs confirmed that vaccination with PA is sufficient to provide protective, though not sterilizing, immunity against B. cereus G9241 (Oh et al, 2013;Palmer et al, 2014). Furthermore, a formaldehyde-inactivated spore and PA preparation generated immunity to Bcbva strains in outbred mice (Brézillon et al, 2015).…”
Section: Vaccinementioning
confidence: 95%
“…DNA prime-protein boost immunization is an attractive strategy in development of a potent vaccination method by eliciting a more robust immune response to different pathogens including virus, bacteria, and parasites [38][39][40][41]. In cancer setting, this strategy could be potentially applicable in induction of protective immune response to poor immunogenic tumor antigens.…”
Section: Discussionmentioning
confidence: 99%